2020
DOI: 10.1002/psp.2376
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for family planning after internal migration: Analysis of Ethiopia 2017–2018 PMA survey data

Abstract: Internal migration's effect on family planning behaviour depends upon migration circumstances. While many studies describe instability and displacement's effect on family planning access, fewer studies consider the positive association between internal migration and family planning behaviour. Using Performance Monitoring for Action (PMA) survey data, we examine the relationship between internal migration and unmet need for family planning in Ethiopia from 2017 to 2018. We describe determinants of family planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Our findings provide evidence that migrant women were less likely to have unmet need for FP than non-migrant women in Bangladesh. This is consistent with studies in Ethiopia and Cotonou of Benin Republic [ 36 , 37 ]. Migration can delay childbearing due to time taken to adjust at the new environment [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings provide evidence that migrant women were less likely to have unmet need for FP than non-migrant women in Bangladesh. This is consistent with studies in Ethiopia and Cotonou of Benin Republic [ 36 , 37 ]. Migration can delay childbearing due to time taken to adjust at the new environment [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Migration can delay childbearing due to time taken to adjust at the new environment [ 38 ]. If migration is particularly to search for opportunity, migration provides easy access and better exposure to contraceptive methods [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that migrating persons may generally have reduced access to health services in Uganda and that contraceptive and HIV programs in Uganda should consider the unique needs of mobile persons [21,28,29]. Unlike migration and ART use, prior literature on the association between migration and contraceptive use in Africa is mixed [29,30]. Multiple studies have found differences in contraceptive use between migrant and non-migrant populations, but these are frequently explained by other characteristics, such as age and fertility intention of individuals and the communities into which migrants and non-migrants live [39,38,40].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, previous studies frequently include women with no need for contraception in their denominators (i.e. looking at contraceptive use generally without accounting for pregnancy desire), and thus cannot determine whether differences in contraceptive behavior are due to differences in fertility intentions between migrants and non-migrants, or other factors, such as access [30,38,39]. Migration may impact contraceptive need and use through disrupting care networks, particularly among users of short-acting contraception (injectable, pill, condom) who rely on regular contact with the health system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation